PERCEIVED EFFECTIVENESS OF CREDIT SERVICES OF DIFFERENT DAIRY SERVICE DELIVERY SYSTEMS IN NAMAKKAL DISTRICT OF TAMIL NADU - S. Karthikeyan (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The present study was conducted in Namakkal District of Tamil Nadu to explore the perceived effectiveness of credit services offered by different dairy service delivery systems. A total of 120 respondents were selected for the study by stratified proportionate random sampling method and the data were collected by personal interview method using pre-tested interview schedule. The respondents predominantly availed the credit facilities from credit service providers like commercial banks and cooperative banks (38.33%) followed by dairy cooperatives (26.67%) while meagre percentage of the respondents received the credit benefit from the milk vendors (5.0%) and private integrators (4.17%). Based on the mean weighted score, the dairy farmers perceived the credit facilities of dairy cooperatives are effective than that of the commercial and cooperative banks in terms of their accessibility, timeliness, interest rate, administrative procedure and their flexibility in repayment.